(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Modern technological evolution fosters the integration of traditional materials with electronic components, and the textile industry is becoming an important part of this trend. Particular attention is drawn to the integration of conductive yarns into knitted fabrics, which opens up new horizons for the development of smart textiles. This article aims to provide a comprehensive review of existing research, technologies, yarn compositions, and application areas, along with an assessment of the challenges and future prospects in this field.